Repositioning universal basic education (UBE) scheme in Nigeria: implications for social transformation (2007)
Nigerian Government had long realized that people needed the right attitudes for the country to achieve the desired development. To this end, the Government committed a huge sum of money to programmes designed for the purpose. Education is a powerful instrument for social transformation. UBE as an education programme was inaugurated seven years ago but still at its impact is yet to be felt. Certain constraints which impeded successful implementation of similar programmes in the past should be identified and realistically tackled in an effort to reposition the present UBE programme. This paper examined the state of UBE scheme and its drive towards health and social transformation. The discussion focused on values of education, UBE and health transformation as well as UBE and social transformation. Effort was made on how to reposition UBE to make it play its role as a tool for health and social transformation.